PENGAWASAN KETENAGAKERJAAN DI BIDANG KESEHATAN KERJA SEBAGAI UPAYA PERLINDUNGAN HUKUM BAGI BURUH - Dimas Karnadi Sofian (Jurnal HUKUM BISNIS, 2018)
The number of problems in the field of labor that is not completed ie one of them with the non-fulfillment of occupational health for workers by employers. As a result, labor is threatened with work-related diseases that are not experienced directly but gradually. In this regard, the government is obliged to provide protection to workers by conducting labor inspection in the field of occupational health. Thus, workers rights in occupational health can be met by employers. Occupational health is one of the important factors to create a conducive business world. In order to support it, the role of government is expected to be more leverage in conducting labor inspection in the field of occupational health. So that the government immediately issued the regulation of labor inspector in the field of occupational health in addition to providing adequate facilities in the supervision process.Keywords : Labor Inspection, Occupational Health, Legal Protection